Ab initio calculation of intermolecular potentials for dimer Cl2–Cl2 and prediction of second virial coefficients - Duoc, Nguyen Thanh; Ai Nhung, Nguyen Thi; Duong, Tran; Tat, Pham Van (Vietnam Journal of Chemistry, 2015)
The results presented in this paper are the ab initio intermolecular potentials and the second virial coefficient, B2 (T) of the dimer Cl2-Cl2. These ab initio potentials were proposed by the quantum chemical calculations at high level of theory CCSD(T) with basis sets of Dunning’s valence correlation-consistent aug-cc-pVmZ (m = 2, 3); these results were extrapolated to complete basis set limit aug-cc-pV23Z. The ab initio energies of complete basis set limit aug-cc-pV23Z resulted from the exponential extrapolation were used to construct the 5-site pair potential functions. The second virial coefficients for this dimer were predicted from those with four-dimensional integration. The second virial coefficients were also corrected to first-order quantum effects. The results turn out to be in good agreement with experimental data, if available, or with those from empirical correlation. The quality of ab initio 5-site potentials proved the reliability for prediction of molecular thermodynamic properties. Keywords. 5-site potentials, second virial coefficients, ab initio energy